A Temporary vs. Permanent Anchored Percutaneous Lead Trial of Spinal Cord Stimulation: A Comparison of Patient Outcomes and Adverse Events. Issue 5 (13th September 2017) - Simopoulos, Thomas; Sharma, Sanjiv; Aner, Moris; Gill, Jatinder S.
Abstract : Objectives: A trial of spinal cord stimulation (SCS) is a prerequisite to determine efficacy of the therapy prior to placement of a permanent implanted system. A trial may be conducted employing a percutaneously placed temporary cylindrical lead or via a permanently anchored cylindrical lead placed and subsequently secured via open surgical method. There has been little investigation comparing the two methods of trial. This study is a comparative analysis of the two methods both for prediction of success as well as associated morbidity. Study Design: Retrospective chart review. Materials and Methods: SCS outcomes of percutaneous temporary lead trial or the temporary lead (TL) group and permanent anchored lead trial or permanent lead (PL) group were analyzed for lack of relief, poor paresthesia coverage, false positive trial phase, fading relief, and biological complications. Results: Outcome data was analyzed for 148 patients in the TL group and 138 patients in the PL group. In comparing the two trial methods, false positive rate of trial was higher ( p  < 0.05) in the PL group as compared to the TL group (6.35 vs. 1.35%). Cumulative wound infections (6.52 vs. 1.35%), and poor wound healing (4.35 vs. 0%) were also significantly higher in the PL group. Rate of success in the trial phase was equal in both groups. Conclusion: The percutaneous temporary lead trial group was associated with fewer false positives and wound related complications as compared to permanent anchored lead trial group. There was very little technical advantage of routinely anchoring the trial lead.